Coffee [videorecording (DVD)] : the drink that changed America - Cycon, Dean, 1953- (Pilot Productions, 2016)
Join coffee roaster and social entrepreneur Dean Cycon, and food lover Judith Jones, as they unravel the secrets behind the one of America's favorite drink, from the bean's discovery in Ethiopia over a thousand years ago to it's transportation to Europe by the Venetians and on to it's eventual arrival in the U.S.